Factors of Pearl Cultivation in Maijuring Village, Aru Tengah District, Aru Islands Regency - Dumgair, Ondry Gerson; Lasaiba, Mohammad Amin; Partini, Dwi (Jurnal Pendidikan Geografi Unpatti, 2023)
Pearl cultivation began to develop, especially in Maluku Province. With the increasing cultivation of pearl mussels, the demand for pearl seeds is also increasing, but this is also hampered by a lack of supply of seeds from wild catches or obstacles during seed production, namely high mortality at the spawning stage and in general the growth and survival of shellfish species is greatly influenced. by important factors, namely temperature and food availability and other important factors, on this basis the author conducted research which aims to determine the aspects of pearl oyster cultivation in Maijuring Village, Aru Tengah District, Aru Islands Regency. The type of research used is Qualitative Descriptive analysis with seawater samples and five pearl oyster cultivators. The sampling technique used is purposive sampling, which uses the criteria of people who cultivate pearl oysters. The data collection techniques used are observation, documentation, and interviews. The data analysis technique used is SWOT analysis. The results of the research show that in Maijuring Village, there are several factors in cultivating pearl oysters, namely water quality, feed availability, water temperature, water depth, water salinity, water pH, population density, cultivation land maintenance such as water quality, which is influenced by temperature, namely 26.9, pH namely 7.76, and salinity 34.42, and depth 20-30m, from the surface.